A comparative experimental study on the impact strength of standard and asymmetric involute spur gears. (February 2021) - Kalay, Onur Can; Doğan, Oğuz; Yılmaz, Tufan Gürkan; Yüce, Celalettin; Karpat, Fatih
Highlights: A novel test rig is designed and manufactured. Different tooth profiles and drop heights are used and compared among themselves. A novel method to measure impact strength of asymmetric involute gears is proposed. Asymmetric profile showed a distinctive advantage in gear impact strength. Abstract: Gears are one of the main components of the power transmission systems and are used in various fields. Problems caused by sudden load changes in mobile systems are frequently encountered today. Gear dynamics have become more influential due to demands of high power transmission capability, long life, and low-cost. However, inertial forces caused by accelerated movements of gear can have unpredictable results. The impact loads must be calculated correctly. It is inconvenient to determine the impact strength of gear via standard drop-weight test rig due to inhomogeneity and complex geometries. This study investigates how the tooth profile affects the impact load on the involute spur gears. For this reason, a special test setup and experimental approach was proposed to examine the influence of the asymmetric profile on the impact strength. It was observed that the peak force values increased by approximately 15.3% when using 20°/30° asymmetric profile gears in comparison with the 20°/20° standard design. This improvement can reach up to 25.8% in terms of peak force energy. The results indicate that the proposed novel test setup and the experimental method can be used for measuring the impact strength of asymmetric involute gears.